Study on the valorization of rice waste by using torrefaction method - Kwo Wei, Teh (2015)
Biomass plays a crucial role as the source of renewable carbon which can be utilised in the production of biofuels to bring about the desired fossil energy independence in the future. However, the raw biomass itself has some undesirable properties such as high moisture content, low energy density and deterioration after a short duration of storing period. Hence, a thermochemical process, commonly known as the torrefaction technology or mild pyrolysis is normally used to preliminary treat the biomass to enhance its physical properties. Torrefaction process is also acknowledged as a valorisation process of biomass. By means of this technology, it not only helps to increase the calorific value of the biomass but also eases the process of storage, transportation, and usage of biomass. In terms of abundance, rice waste is one of the vital biomass contributors in Asia. Rice is the primary calorific source for mankind and its significance is comparable to maize, sorghum, wheat, barley and the other major crop grasses from the family Poaceae (Gramineae). In Malaysia, an enormous amount of biomass is generated annually after the harvesting of rice. As for this study, the objective is to investigate the effect of torrefaction on the physical characteristics of the rice waste at different temperature. The torrefaction is carried out at 220°C, 250°C and 280°C with the heating rate of 15°C/min and residence time of 30min. Generally, moisture content, calorific value characterization as well as constituents’ degradation under different temperatures will be inspected on both the raw and torrefied biomass to reveal the effect of torrefaction on the biomass. The preliminary results show that the moisture content of rice husk is 6.53wt% while rice straw is 8.31wt%. The slight deviation from the literature source is deemed to be reasonable due to different pre-drying period. Next, from the experimental results, it is noticeable that torrefaction increases the calorific value of the biomass by 3-17% for rice husk and 4-20% for rice straw. At the same time, it also removed all the moisture content in the rice biomass. The mass yield of the torrefied rice-based biomass is between 78.98-91.20% for rice husk and 82.28-89.85% for rice straw. Meanwhile, the energy yield for rice husk is in the range of 92.51-95.41% and 93.77-98.83% for rice straw after torrefaction. Diagnosis on the physical characteristics of the torrefied biomass is accomplished through Thermogravimetric (TGA) analysis and Fourier Transform Infrared (FTIR) Spectroscopy. In conclusion, the aim of this study is achieved by proving that 250°C is the optimum torrefaction temperature for the conversion of rice waste into valuable biofuels.